Heat transfer model to study nano fluids & its application. (2021) - Shilpi,; Vasishth, Ajay; Aggarwal, Nupur
Abstract: With enormous improvisations in nanotechnology field, a heat transfer in Nano fluid become gorgeous phenomena and their thermal conductivity measurement are more attractive concept then conventional heat transfer mechanism in fluids. Tactlessly the enhancement of thermal conductivity in Nano fluids unable to explain by conventional model. When nanoparticles are suspended in a fluid, at very low concentration it can enhanced thermophysical properties and heat transfer performance. In this review article we will discussed various method to synthesis Nano fluids and its thermo physical properties and applications.